Strategi Gerakan Cegah Stunting Menggunakan Metode Sosialisasi di Desa Darakunci, Kabupaten Lombok Timur: Strategi Gerakan Cegah Stunting Menggunakan Metode Sosialisasi di Desa Darakunci, Kabupaten Lombok Timur - Fitri, Nurul; Widiawati, Nabila; Ningtyas, Risma Pramudia; Sarnyoto, Farah Dhiyah Alfini; Nisa, Waridatun; Ibnistnaini, Wahyu; Ardha, Muhammad Dhani; Aima, Qurratul; Salmanto, Salmanto; Novitasari, Sopia; et al. (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2022)
ABSTRACT Indonesia still has a fairly high stunting prevalence rate, which is 24.4% and is still at the standard number tolerated by WHO, which is below 20%. This is due to the high rate of anemia and malnutrition in adolescent girls before marriage, so that during pregnancy they produce stunted children. Stunting is a condition of growth and development failure experienced by children due to lack of nutritional intake for a long time, repeated infections, and inadequate psychosocial stimulation, especially in the first 1000 days of life. In the short term, specific and sensitive nutrition interventions need to be optimized, while the long term strategy needs to be intensified with opportunities for collaboration between sectors and multistakeholders to ensure sustainability and achieve the stunting reduction acceleration target. In addition, it is necessary to implement the Public Private Partnership strategy in an effort to enforce governance, a commitment to operational elaboration is needed to ensure the stunting prevention program for rural toddlers at 1000 HPK.